Sistema de monitoreo perlas para la toma de decisiones en la Coac Fernando Daquilema Ltda, período 2017-2018 - Calle Riera, Carmen Alexandra (2021)
ABSTRACT This research project was carried out by applying the Perlas Monitoring System at the Savings and Credit Cooperative “Fernando Daquilema” Ltd in 2017-2018. In order to determine the frequency in taking decisions by management using the application of the financial indicators proposed by this system. This work was developed through 5 chapters: Chapter I holds in the referential framework, the statement of the problem, formulation of the research question, justification, objectives, and the hypothesis. Chapter II includes state of the art and generalities of the COAC as historical review, mission, and vision, theoretical foundation emphasizing the variable of the study of the PERLAS System. Chapter III refers to the methodological framework considered in the present work as the method, approach, type, level of investigation, population determination, sample, and the techniques and instruments for data collection and interpretation. Chapter IV contains the results and strategies of applying the PERLAS Monitoring System, which was developed based on the information provided from the Statements of Financial Position and Statements of Comprehensive Income in the years 2017 and 2018. Finally, in the chapter V the conclusions and recommendations were raised regarding the objectives proposed when this research started. As a result, the application of this system is essential because it evaluates critical or problematic situations within the area of a Cooperative with more effective results. Keywords: Financial analysis, PERLAS Monitoring System, Financial indicators, Taking decisions, Segment 2, Saving and Credit Cooperative. Reviewed by: Mgs. Hugo Romero ENGLISH PROFESSOR c.c. 0603156258